2009
DOI: 10.1177/0891243208326529
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Doing Gender

Abstract: W e're delighted to have "Doing Gender" and its sequelae as the subjects of this symposium. The serious readings of our work by Professors Connell, Jones, Kitzinger, Messerschmidt, Risman, Smith, and Vidal-Ortiz do us honor, and we welcome the chance to address them. We use our response to reflect on, clarify, admit, and expand on what we said originally and what we have said since. As important as the path taken, however, is the theoretical path ahead, and we will comment on that as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
503
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 608 publications
(525 citation statements)
references
References 30 publications
9
503
0
13
Order By: Relevance
“…While the equestrian social world is often thought to be socially conservative (Fletcher and Dashper, 2013), a number of researchers have suggested that in relation to gender, equestrianism may in fact offer small and subtle challenges to wider restrictive gender regimes (Birke and Brandt, 2009;Plymouth, 2012;Dashper, 2013). In the sections below I use a number of examples to illustrate how involvement in the horse world offers opportunities for gender to be done and, sometimes, 'redone' (West and Zimmerman, 2009;Connell, 2010).…”
Section: Research Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…While the equestrian social world is often thought to be socially conservative (Fletcher and Dashper, 2013), a number of researchers have suggested that in relation to gender, equestrianism may in fact offer small and subtle challenges to wider restrictive gender regimes (Birke and Brandt, 2009;Plymouth, 2012;Dashper, 2013). In the sections below I use a number of examples to illustrate how involvement in the horse world offers opportunities for gender to be done and, sometimes, 'redone' (West and Zimmerman, 2009;Connell, 2010).…”
Section: Research Approachmentioning
confidence: 99%
“…In such ways, traditional feminine roles are done and, to some extent, redone (West and Zimmerman, 2009). Although their expertise may not be comparable with that of many farmers, horse women demonstrate knowledge about the land, and an ability to manage and transform the land to suit their own needs and those of their horses.…”
Section: Relationships To the Landmentioning
confidence: 99%
“…Przegląd socjologicznych prac poświęconych płci pokazuje, że ta bywa konceptualizowana jako rola społeczna i zbiór oczekiwań (Norris, inglehart 2008(Norris, inglehart ), tożsamość (np. titkow 2007Bem 2000), jako performans (Butler 2008), działanie (martin 2006;West i zimmerman 1987;West i zimmerman 2009) czy jako zewnętrzna i opresyjna struktura społeczna (Delphy 2007a(Delphy , 2007b. z jednej strony jest wyjaśniana ona jako cecha relacji społecznych, która odnosi się do indywidualnej różnicy zauważalnej między osobami.…”
unclassified
“…znamienny przykład podaje Chris Brickell (Brickell 2006: 89), wskazując na niezwykłą popularność wśród współczesnych socjologów płci koncepcji performatywności zaproponowanej przez Judith Butler. zdaniem autora analiza konstrukcjonistycznej koncepcji Butler jednoznacznie wskazuje na jej kompatybilność z założeniami sformułowanymi o wiele wcześniej w teoriach interakcjonizmu symbolicznego i etnometodologii (West i Zimmerman 2009;West i Zimmerman 1987), do których to jednak ani Butler (ani wielu jej kontynuatorów) nie nawiązuje lub nawiązuje pobieżnie.…”
unclassified
“…Thus, gender becomes a way of acting like a doctor or of driving a car" (2009:10). We show how being female is foregrounded as a threat and a problem, in many ways divorced from the realities of how female medics actually do gender (West and Zimmerman 2009) in their chosen profession. This is interwoven with a background gendered identity of the ideal medic, who is one hundred percent committed to the profession, thus allowing less blatant but still pervasive questioning of the legitimacy of female medics.…”
Section: Introductionmentioning
confidence: 99%